High-resolution spatial analysis of a z ∼ 2 lensed galaxy using adaptive coadded source-plane reconstruction. Issue 2 (29th August 2018) - Sharma, Soniya; Richard, Johan; Yuan, Tiantian; Gupta, Anshu; Kewley, Lisa; Patrício, Vera; Leethochawalit, Nicha; Jones, Tucker A
ABSTRACT: We present spatially resolved analysis of a lensed galaxy, SDSS1958+5950 at z = 2.225, from the Cambridge Sloan Survey of Wide Arcs in the Sky. We use our new high-resolution imaging data to construct a robust lens model for the galaxy group at z = 0.214. We employ the updated lens model to combine the Integral Field Spectrographic observations on two highly distorted images of the lensed target. We adopt a forward-modelling approach to deconvolve the effects of point spread function from the combined source-plane reconstruction. The approach is adapted to the lens model magnification and enables a resolution of ∼170 pc in the galaxy-source plane. We propose an ongoing merger as the origin of the lensed system on the basis of its source-plane morphology, kinematics and rest-frame emission-line ratios. Using our novel technique of adaptive coadded source plane reconstruction, we are able to detect different components in the velocity gradient that were not seen in previous studies of this object, plausibly belonging to different components in the merging system.